2009
DOI: 10.3340/jkns.2009.45.3.143
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Functional Recovery and Mortality of Surgically Treated Traumatic Acute Subdural Hematomas in 256 Patients

Abstract: Objective : The purpose of this study was to investigate the reliable factors influencing the surgical outcome of the patients with traumatic acute subdural hematoma (ASDH) and to improve the functional outcome of these patients. Methods : A total of 256 consecutive patients who underwent surgical intervention for traumatic ASDH between March 1998 and March 2008 were reviewed. We evaluated the influence of perioperative variables on functional recovery and mortality using multivariate logistic regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 35 publications
3
47
2
2
Order By: Relevance
“…Several authors reported that older age is associated with a higher mortality for TBI (10,14,18,19,27,29,46). Our age data conflicts with prior studies.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…Several authors reported that older age is associated with a higher mortality for TBI (10,14,18,19,27,29,46). Our age data conflicts with prior studies.…”
contrasting
confidence: 56%
“…Intraoperative acute brain swelling seems to be a strong predictor of poor outcome for the patients with TBI (18,24,41 …”
Section: █ Conclusionmentioning
confidence: 99%
“…5,10,13,20 There may be underlying physiologic basis to account for the increased mortality observed with craniectomy. Removal of the bone segment allows for expansion of swollen brain through the defect leading to axonal stretch.…”
Section: Discussionmentioning
confidence: 99%
“…13,35 However, current advances in imaging, rapid diagnostics, medical management of hemodynamic properties, and surgical techniques have improved patient outcomes, 36 and a further decrease in mortality associated with treatment for intracranial bleeding has been demonstrated; in 2008, postoperative mortality associated with craniotomy for evacuation of acute subdural and epidural hematoma ranged from 22% to 41%. 17,33,34 It is plausible that this overall decrease in mortality may also be reflected by improved survival among older patients. Given the breadth and scope of medical and surgical advancements, this raises an interesting and valuable question: Do older patients continue to suffer higher morbidity and mortality rates than younger patients following evacuation of intracranial hematoma and/or hemorrhage?…”
mentioning
confidence: 99%